Flexible, frugal, and fast carbon dioxide sensing by bismuth ferrite-silver nanowires - Sanjeev Patil; A. Sudha; Parasuraman Swaminathan (Next Materials)
Carbon dioxide (CO2) is the prime contributor to climate change making detection of this gas crucial. Typical chemiresistive CO2 sensors operate at high temperatures requiring additional heating elements. These sensors are also rigid since most flexible substrates would not be able to operate at these temperatures. In this work, a composite of bismuth ferrite nanoparticles (BFO NPs) and silver nanowires (Ag NWs) is developed towards room temperature chemiresistive sensing of CO2. The composite is prepared as a stable dispersion and deposited by direct ink writing on a flexible polyethylene terephthalate (PET) substrate. The sensor displays response times of 7.2 s and 7.7 s, in straight and bent configurations, respectively for 300 ppm CO2. Thus, we report a significant step towards development of a room temperature flexible, frugal, fast, and low-powered CO2 sensor.